Optical Coherence Tomography Angiography Findings in Stargardt Disease - Mastropasqua, Rodolfo; Toto, Lisa; Borrelli, Enrico; Di Antonio, Luca; Mattei, Peter A.; Senatore, Alfonso; Di Nicola, Marta; Mariotti, Cesare (PloS one, 2017)
to assess vessel density of superficial capillary plexus (SCP), deep capillary plexus (DCP) and choriocapillaris (CC) in advanced Stargardt disease (STGD) using optical coherence tomography angiography (OCTA) and correlate these findings with macular function using pattern electroretinogram (PERG) and multifocal electroretinogram (mfERG). Twelve patients (24 eyes) with advanced STGD underwent vessel densities and macular thickness measurements using OCTA. A control group of 24 healthy controls (24 eyes) was chosen for comparison. In the STGD group correlation between vessel density and macular thickness and between macular function and morphologic parameters were evaluated. Whole parafoveal vessel density (VD) of SCP was significantly lower in STGD group compared to the control group (p<0.05). Foveal VD and whole parafoveal VD of the DCP were significantly lower in STGD group compared to the controls (p<0.05). CC was significantly decreased in STGD compared to controls (p<0.05). Foveal macular thickness (MT), full parafoveal MT, and inner limiting membrane (ILM)-inner plexiform layer (IPL) parafoveal MT thickness were decreased in STGD eyes compared to controls (p<0.001). PERG and mfERG were both significantly reduced in STGD compared to controls (p<0.001). A direct correlation was found between full parafoveal MT and vessel density in the STGD group. Patients with advanced STGD showed a reduction of SCP, DCP and CC compared to healthy eyes related to a reduction of total and ILM-IPL macular thickness. These results suggest that both retinal capillaris plexuses and choriocapillaris reduction occur in STDG along with inner and outer retinal thinning.